1991
DOI: 10.1021/tx00023a012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of [14C]benzyl selenocyanate in the F344 rat

Abstract: Benzyl selenocyanate (BSC), a synthetic organoselenium compound, has been shown to inhibit chemically induced tumors in several animal model systems. However, it is not known whether BSC or one of its metabolites is responsible for the chemopreventive effect. An initial approach to this question requires the structural elucidation of BSC metabolites in vitro and in vivo. To determine the structures of BSC metabolites in vitro, we studied the metabolism of [14C]BSC using Aroclor-induced rat liver 9000g supernat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…There are many reports of experimental evidence that selenium supplementation can reduce the incidence of many types of cancer when nontoxic doses are provided to the diet of rodent species (9,10). Epidemiological studies have identified low selenium levels as one of several factors that are associated with an increased risk of prostate cancer (11,12), but not all studies have shown this relationship (6,13).…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports of experimental evidence that selenium supplementation can reduce the incidence of many types of cancer when nontoxic doses are provided to the diet of rodent species (9,10). Epidemiological studies have identified low selenium levels as one of several factors that are associated with an increased risk of prostate cancer (11,12), but not all studies have shown this relationship (6,13).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, the reaction was compatible with most of the studied alkenes except bicyclo[2.2.1]hept-2-ene (1j), which provided the corresponding 2-acetoxy-1-selenenylation compounds in good to excellent yields (entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It was also determined that the groups on the benzene ring, no matter whether they were electron-donating or electron-withdrawing groups, did not influence the yield (entries 2-7, 13, 14).…”
Section: Resultsmentioning
confidence: 70%
“…When treated under the same conditions, the addition to cyclohexene (1i) and 1j proceeded in a trans fashion and the single stereoisomers were isolated with an excellent yield for 3i (entry 9) and a poor yield for 3j due to the steric hinderance effect of the methylene group (entry 10). Compared with 2a, the dibenzyl diselenide (2b), an aliphatic diselenide, also reacted easily with alkenes, but the yields were slightly lower (entries [12][13][14]. From Table 2, it is obvious that the yields for most products 3 were higher when KBr was used as catalyst as opposed to NaCl, so the catalytic effect of KBr is better than NaCl in the acetoxyselenenylation of alkenes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations